Counseling to Improve Service Quality and Effective Participation Between Teachers and Parents - Dyah Erlina Sulistyaningrum; Sunarso Sunarso; Dendy Eta Mirlana; Amrih Yuwono; Mohammad Achwan; Abdul Halim; Tri Rahayuningsih; Suryadi Suryadi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
A harmonious and effective relationship between teachers and parents is a crucial factor in supporting the success of the educational process in schools. However, in practice, gaps in communication, a lack of active participation from parents, and limited understanding of each party’s role in supporting student development are still common. This outreach program aims to improve the quality of teacher-parent communication and to encourage more active and effective parental involvement in the educational environment. The methods used in this program include lectures, interactive discussions, and case study simulations. The results show that the program successfully increased the understanding of both parties regarding the importance of collaboration, openness, and two-way communication in supporting the teaching and learning process. With improved service quality from teachers and active engagement from parents, it is expected that a stronger synergy in children's education at school can be achieved.